Mranʻ māʹ Chuirhayʻlacʻ Lamʻʺ cañʻ Pātī Pathama ʼa krimʻ mrokʻ Ññī lā khaṃ e* Praññʻ thoṅʻ cu Mranʻ mā Nuiṅʻ ṅaṃ cīʺ pvāʺ tuiʺ takʻ reʺ ʼa tvakʻ cī maṃ kinʻʺ khya mhatʻ lupʻ choṅʻ rā n* luikʻ nā ranʻ lamʻʺ ññvhanʻ mhu myāʺ (Mranʻ māʹ Chuirhayʻlacʻ Lamʻʺ cañʻ Pātī, 1971)
Directives for economic planning in Burma, laid down by the Burma Socialist Programme Party at its first conference in 1971.